Psychopathological Symptoms under Smog: The Role of Emotion Regulation - Chen, Shuquan; Kong, Jiayang; Yu, Feng; Peng, Kaiping (Frontiers in Psychology, 2018)
Over the past decade, major cities in China have suffered from severe air pollution, which is also known as smog. Despite lay considerations that smog might pose risks for psychopathology, it remains unknown whether it is only linked to affective psychopathology or to a broader range of symptomologies. Moreover, whether individual differences in emotion regulation, a transdiagnostic risk factor for psychopathology, would influence the magnitude of pollution-induced symptoms is not well understood. Using a longitudinal design, the current study measured use frequencies of emotion regulation strategies and psychopathological symptoms in a sample of university students at Time 1 (without smog, N = 120) and then reassessed for psychopathology at Time 2 (after acute exposure to smog for one week, N = 102). The results showed that participants had higher levels of positive symptom distress, obsessive-compulsive symptoms, interpersonal sensitivity, depression, and psychoticism at Time 2. Moreover, reappraisal is negatively associated with smog-induced elevations in psychopathological symptoms only when participants rely heavily on suppression. We discuss the implications of this investigation for both intervention efforts and future work on the contextual factors surrounding the deployment of emotion regulation strategies.